A Comparative Performance Analysis of Fog-Based Smart Surveillance System - Shrestha, Sujan; Shakya, Subarna (Journal of Trends in Computer Science and Smart Technology, 2020)
There has been increasing demand of security and safety in public as well as private places and hence surveillance system using IoT sensors, cameras has become the most important part in our daily life. This system has to operate all times 24/7/365 and thus produces huge amounts of data. Cloud computing offers storage, processing, and analytical services for handling of such massive amounts of data. For real time applications like smart surveillance system, increased latency from centralized Cloud computing is not acceptable. Fog Computing is an extension of Cloud computing, evolved to minimize latency. A Fog-Based Smart Surveillance System has been modelled and simulated in two environments as Cloud Only Network and Fog-Based Cloud Network using iFogsim. Various performance metrics like Application Loop Delay, Energy Consumption, Execution Cost, and Network Usage has been compared between Fog-Based Cloud Network and Cloud Only Network. Results showed that Fog-Based Cloud Network performs better than Cloud Only Network.
Keywords: Fog Computing; Smart Surveillance System; IoT; Application Loop Delay; Energy Consumption; Execution Cost; Network Usage; iFogSim